Identification of Subsurface Structures Using Topex Altimetry Satellite Gravity Data: Implications for Preliminary Surveys of Geothermal Existence - Dwi Anggraeni; Rahmat Nawi Siregar; Sismanto Sismanto (CV FOUNDAE, 2023)
Bangka Island is on the Sunda Shelf (Eurasian tectonic plate) and the outer part of the Sumatra basin. Plate tectonic activity results in fault structures and forms the statigraphy of rock formations such as Alluvium, Ranggam, Klabat Granite, Tanjung Genting, and the Pemali Complex. The fault structure was identified as a control structure for the radiogenic geothermal system. Radiogenic geothermal heat originates from the decay of radioactive elements in granite rocks (Klabat Granite formation) on Bangka Island. The purpose of this research is as a preliminary survey of the presence of Slag and Cracker geothermal energy on Bangka Island using the gravity method. The research data used is secondary data obtained from the Topex satellite (Topography Experiment). The results of the modeling show that many fault structures in the study area are found around the Slag and Cracking geothermal manifestations. The fault structure is also accompanied by a breakthrough by the lower layer of rock into the rock above it. So that the fault structure can control the Slag and Crack radiogenic geothermal system.